Bundling Public with Private Goods - Gerrit Frackenpohl; Gert Pönitzsch (University of Bonn, Bonn Graduate School of Economics (BGSE), 2013)
We propose a simple mechanism that might improve voluntary contributions to public goods. Using a laboratory experiment we analyze how bundling public with private goods affects individuals' valuations for both goods. In the experiment, subjects may purchase a private and a public good either separately or in the form of a bundle. The data show superadditivity for bundles of public and private goods, i.e., the willingness to pay for the bundle exceeds the willingness to pay for the two separate goods. In contrast, we find no superadditivity in control treatments with only private goods. We discuss several behavioral concepts which are in line with our results as well as implications for fundraisers and firms.
Keywords: C91; D12; H41; 330; Public Goods; Bundling; Valuation; Superadditivity